Decolonising the Humanities: Reimagining Black Intellectual Life and Personhood in Southern African Contexts - Sandwith, Corinne (PINS-Psychology in Society, 2024)
This review article explores possibilities for transdisciplinary entanglements between the disciplines of critical psychology and literary criticism through a reading of the volume, ʻFoundational African Writers’, edited by Bhekizizwe Peterson, Khwezi Mkhize and Makhosazana Xaba. In this article, ‘Foundational African Writers’ is approached as a distillation of Peterson’s investment in excavating the world-making activities, writing lives and activities of ordinary people as a central dimension of the project to decolonise the Humanities. As this edited volume attests, Peterson’s creative and critical oeuvre continues to provoke thinking about the ways in which the reading of the African literary archive can assist in the wider project of decolonising and re-imagining intellectual and creative history in the Global South while also providing opportunities for new modes of thinking about personhood and psychic life in contexts of precarity, intergenerational trauma and economic exclusion.